Imaging of the Heart: Potential Application to Alcohol-Induced Heart Disease - Bergmann, Steven R. (Alcohol Health Res World, 1995)
In addition to its effects on the brain and other organs, chronic heavy alcohol use can lead to cardiovascular diseases including hypertension. Another consequence of heavy drinking is alcohol-induced heart muscle disease, which leads to a diminished pump function of the heart. Several mechanisms related to alcohol and its metabolism in the body can contribute to alcohol-induced heart muscle disease by interfering with the heart’s metabolism and energy production and thereby impairing heart muscle function. Noninvasive imaging techniques can help researchers and clinicians to monitor alcohol’s effects on the heart and its metabolism. For example, one study found that increasing amounts of alcohol reduced the uptake of fatty acids—the primary fuel used by the heart muscle—into the heart. Other investigators have demonstrated that the heart’s metabolism of fatty acids is impaired in patients with alcohol-induced heart muscle disease. Although the potential of imaging techniques for studying alcohol-induced heart muscle disease has not yet been fully explored, these approaches are likely to play an increasingly important role in the future.